Service Robot Acceptance Among Customers of Insurance in Kathmandu Valley - Aryal, Nijita (SAIM Journal of Social Science and Technology, 2025)
Purpose: Service robots equipped with automation and artificial intelligence, especially generative AI, are increasingly integrated into service interactions worldwide. Despite their advanced capabilities, research on factors influencing customer acceptance of service robots remains limited. To examine the acceptance of service robots among insurance customers in Kathmandu Valley, Nepal, using the sRAM framework. Design/Methodology/Approach: A crosssectional survey collected data from 243 insurance customers in Kathmandu Valley using selective sampling. Hypotheses were tested employing SPSS statistical analysis. Findings: Perceived Ease of Use (PEOU) and Subjective Social Norms (SSN) significantly impact customer acceptance of service robots. Similarly, Perceived Social Influence (PSI) and Robot Anxiety Perception (RAP) also have a significant positive influence. However, Perceived Usefulness (PU), Perceived Humanness (PH), Perceived Social Norms (PSN), and Trust (TR) showed no significant effect on acceptance among these customers. Practical Implications: This study enriches the literature on service robot adoption and offers actionable insights for Nepal’s insurance industry to optimize the deployment of robotic services. Originality: Among the first studies to investigate service robot acceptance specifically within Nepal's insurance customer context.